Air quality in wood-based small and medium enterprises in Selangor / Noradila Mohamed ... [et al.]. - Mohamed, Noradila; Mohd Aminuddin, Murni Amirra; Ismail, Zitty Sarah; Mohd Yasim, Nurzulaifa Shaheera Erne; Nik Ariffin, Nik Azlin (2018)
Wood-based Industries was known to generate various airborne pollutants such as wood and dust. This study was conducted to determine air quality in wood-based Small and Medium Enterprises (SMEs) in Malaysia. The determination of total dust and respirable dust was conducted based on National Institute of Occupational Safety and Health (NIOSH) 0500 and 0600. Study found that 38.1% (n=16) of the total dust exceed 5 mg/m³ in Schedule 1 of USECHH 2000. None of the respirable dust concentration exceeds 5 mg/m3 of wood dust concentration by Schedule 1 of USECHH 2000 and OSHA but 4.8% (n = 2) had exceed 3mg/m3 by ACGIH. In conclusion, dust and total volatile organic compound was found in wood-based SME where few total dust concentrations for both workplace environment level had exceeded 5mg/m3 but none was seen for respirable dust concentration.